The anterior thalamus provides a subcortical circuit supporting memory and spatial navigation - O‘Mara, Shane M. (Frontiers in Systems Neuroscience, 2013)
The anterior thalamic nuclei, a central component of Papez’ circuit, are generally assumed to be key constituents of the neural circuits responsible for certain categories of learning and memory. Supporting evidence for this contention is that damage to either of two brain regions, the medial temporal lobe and the medial diencephalon, is most consistently associated with anterograde amnesia. Within these respective regions, the hippocampal formation and the anterior thalamic nuclei (anteromedial, anteroventral, anterodorsal) are the particular structures of interest. The extensive direct and indirect hippocampal-anterior thalamic interconnections and the presence of theta-modulated cells in both sites further support the hypothesis that these structures constitute a neuronal network crucial for memory and cognition. The major tool in understanding how the brain processes information is the analysis of neuronal output at each hierarchical level along the pathway of signal propagation coupled with neuroanatomical studies. Here, we discuss the electrophysiological properties of cells in the anterior thalamic nuclei with an emphasis on their role in spatial navigation. In addition, we describe neuroanatomical and functional relationships between the anterior thalamic nuclei and hippocampal formation.